Straniamenti e spaesamenti di Luigi Gualdo: Personaggi e luoghi tra ideale e realtà, cosmopolitismo e sradicamento - Fonio, Filippo (Incontri. Rivista europea di studi italiani, 2021)
Estrangement and Out-of-Placeness in the Works of Luigi Gualdo Characters and places between ideal and reality, cosmopolitanism and uprooting This paper focuses on the different forms of estrangement and out-of-placeness which can be found in Luigi Gualdo’s works. Gualdo (1844-1898) was a prominent writer whose works are influenced by French realism and Parnasse, Italian scapigliatura and the European decadence and estheticism. Moreover, he lived between France and Italy and he was one of the main passeurs between French and Italian literature of his time. This particular condition of the writer is reflected in his works and in particular in the portraiture of his characters, which are often rootless artists and mundane women with a strong component of cosmopolitism. The aim of this paper is to analyse some of the characteristics and features of Gualdo’s characters according to the parameters of estrangement and out-of-placeness. In particular I will focus on the ambiguous nature of the relation between ideal world and reality, of artistic genius and its place in society and the normal world, as well as on more specific topics related to the subject, such as spleen, places described as theatrical decors, hotel rooms and feminine nomadic attitudes, cosmopolitism as both a challenge and an opportunity for the characters. I will conclude on a specific issue regarding the struggle between the estranged character, time, and aging.